Improving sustainability literacy of future quantity surveyors. Issue 4 (21st November 2016) - Xia, Bo; Rosly, Nur; Wu, Peng; Bridge, Adrian; Pienaar, Josua
Abstract : Purpose: The increasing need for sustainability-literate construction professionals has prompted higher education institutions to incorporate a sustainability agenda education into their construction courses. The purpose of this paper is to investigate the sustainability knowledge embedded into a quantity surveying (QS) undergraduate course. Design/methodology/approach: Using the Queensland University of Technology (QUT) as a case study, analysis of sustainability knowledge embedded into the QS course is conducted by examining the content of QS course structure, unit aims, learning outcomes, assessment framework and weekly lecture and tutorial materials. Findings: The results show that the "incorporation approach", i.e. the practice of incorporating the sustainability themes into existing relevant subjects, is mainly used in delivering the sustainability knowledge to the QS students. Additionally, it is found that in its QS course, QUT has covered all aspects of sustainability comprehensively from an environmental viewpoint and with regard, to economic, social and governance aspects. Practical implications: This research also proposes recommendations for further improvement of the sustainability education in the QUT QS course and beyond. Originality/value: This study revealed the current practices and approaches of incorporating sustainability knowledge into QS education programme and addressed the knowledge requirements of future sustainability literate QS professionals.